Relationship of Histopathological Grading and Age of HER2-type Breast Cancer Patients at Adam Malik Hospital in January 2022 – June 2024 - Tuelah, Giselle Iona Rachel; Lubis, Heny Syahrini; Feriyawati, Lita; Harahap, Feby Yanti (SCRIPTA SCORE Scientific Medical Journal, 2025)
Background: Breast cancer is one of the most common cancers that can cause death in Indonesia. Nottingham grading (grade 1, grade 2, and grade 3) in histopathological examination aims to assess tumor activity and prognosis. Other examination includes immunohistochemistry of biomarkers such as estrogen (ER), progesterone (PR), and HER2 receptors. Breast cancer based on its molecular subtypes is classified into luminal A, luminal B, HER2, and triple-negative. HER2-type breast cancer tends to be more invasive with a poor prognosis and susceptible to recurrence and metastasis. Objectives: This study aims to determine the relationship between histopathological grading and age of patients with HER2-type breast cancer. Methods: This is a non-experimental analytical research with cross-sectional approach using the total sampling technique. Secondary data were taken from medical records of breast cancer inpatients at Adam Malik Hospital (January 2022 - June 2024) and analysed using Fisher’s exact test. There were 492 inpatient cases of breast cancer, of which 195 were performed an immunohistochemistry examination and 61 cases were HER2-type. The study sample included 54 patients with fulfilled inclusion criteria. Results: HER2-type breast cancer identified was 31,3%. The most frequent characteristics included female, age ≥45 years, obese nutritional status, and no family history. Poorly differentiated tumors were the most common (38,9%). Result of Fisher’s exact test showed p=0,044 (p<0,05) and OR=0,134. Conclusion:There is a relationship between histopathological grading and age of patients with HER2-type breast cancer. Keyword: breast cancer, HER2, histopathological grading, immunochemistry, molecular subtypes Pendahuluan: Kanker payudara merupakan salah satu jenis kanker yang dapat menyebabkan kematian dan paling sering terjadi di Indonesia. Pemeriksaan histopatologi perlu dilakukan untuk menilai aktivitas tumor dan prognosis. Pemeriksaan lainnya meliputi pemeriksaan imunohistokimia terhadap biomarker seperti reseptor estrogen (ER), progesteron (PR), dan HER2. Kanker payudara tipe HER2 cenderung lebih invasif dengan prognosis yang buruk dan rentan terhadap kekambuhan serta metastasis. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara grading histopatologi dengan usia penderita kanker payudara tipe HER2. Metode: Penelitian ini berjenis analitik non-eksperimental dengan pendekatan cross-sectional yang menggunakan teknik total sampling. Data sekunder diambil dari rekam medis pasien rawat inap kanker payudara di RS. Adam Malik (Januari 2022 – Juni 2024) dan dianalisis menggunakan uji Fisher’s exact. Sampel penelitian ini mencakup 54 pasien yang telah memenuhi kriteria inklusi. Hasil: Kasus kanker payudara yang teridentifikasi tipe HER2 didapati sebesar 31,3%. Karakteristik yang lebih banyak dijumpai meliputi perempuan, usia ≥45 tahun, status gizi mengalami obesitas, dan tanpa riwayat keluarga. Tumor dengan diferensiasi buruk menjadi derajat yang paling banyak ditemukan (38,9%). Hasil uji Fisher’s exact menunjukkan nilai p=0,044 (p<0,05) dan OR=0,134. Kesimpulan: Terdapat hubungan antara grading histopatologi dengan usia penderita kanker payudara tipe HER2. Kata Kunci: grading histopatologi, HER2, imunohistokimia, kanker payudara, subtipe molekuler